Examining the impact of top Malaysian brands' social media marketing on customer engagement: using big data analytics - Abdul Rahman, Wan Nurhayati (2020)
Recognizing the benefits from social media in customer engagement, firms started to realize the importance of social media integration within their marketing plans. However, a lot of these companies still find it challenging to understand what kind of content they should produce on their social media accounts that can positively influence their customer behavior. While previous research has looked into factors that can influence customer engagement, studies on Instagram remains underexplored despite its increase in popularity among the biggest group of consumers, Millennials. Prior research on Instagram also has been focusing on the contribution type of customer engagements such as the likes and the comments, and the studies on holistic view of customer engagement is scarce. Research on Malaysian brands are also limited. This study uses big data analytics to investigate how top Malaysian brands’ social media marketing impact customer engagement. By employing big data analytics, this research extract datasets from 9270 Instagram posts from 4 public Instagram accounts of notable Malaysian brands using SrapeStorm web scraper and analyze them using Microsoft Excel, SAS Text Analytics and IBM SPSS Statistics software. Findings from this research demonstrate how different features of social media marketing affect consumer engagement differently. Creator-related feature, such as founders who are famous or social media influencers, has positive impact to consumption (passive) and creation (active) types of customer engagement. Contextual feature such as post frequency has negative correlation to the contribution type of customer engagement rate. For visual content feature, video contributes greater engagement rate followed by images with people and images without people. Malaysian consumers who follow brands’ Instagram accounts also reacted positively to informative content as shown from the analysis on textual content in this study. Outcomes from this study have significant implications to the elaboration of uses and gratifications theory together with providing additional management insights to a more efficient social media marketing strategy.